2008
DOI: 10.1177/1940161208319650
|View full text |Cite
|
Sign up to set email alerts
|

Media in the Game of Politics: Effects of Strategic Metacoverage on Political Cynicism

Abstract: This study examines the effects of generic strategy news, self-referential press news, and “spin” spotlighting publicity coverage on political cynicism, against the backdrop of governance and policy. Drawing on data from two experiments allowing for replication within a single study, the authors demonstrate that exposure to both generic and publicity strategy news aroused political cynicism relative to issue-based news. In addition, the authors found positive interactions between political knowledge and strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 38 publications
3
51
0
4
Order By: Relevance
“…For example, research in the US and UK has found it to be strongly influenced by political media campaigns (e.g. Cappella & Jamieson, 1996;Vreese & Elenbaas, 2008), and it appears to have a complex relationship with voting behavior, interacting with variables such as the social status of one's group and the perception of opportunity for political change (Southwell & Pirch, 2003). Interest in politics and political cynicism are, therefore, distinct constructs that have different consequences for political involvement (Bynner & Ashford, 1994;Henn, Weinstein, & Wring, 2002).…”
Section: Four Varieties Of Education Effectmentioning
confidence: 99%
“…For example, research in the US and UK has found it to be strongly influenced by political media campaigns (e.g. Cappella & Jamieson, 1996;Vreese & Elenbaas, 2008), and it appears to have a complex relationship with voting behavior, interacting with variables such as the social status of one's group and the perception of opportunity for political change (Southwell & Pirch, 2003). Interest in politics and political cynicism are, therefore, distinct constructs that have different consequences for political involvement (Bynner & Ashford, 1994;Henn, Weinstein, & Wring, 2002).…”
Section: Four Varieties Of Education Effectmentioning
confidence: 99%
“…2 The distinction in the definition of political cynicism between competence and integrity of politicians as two dimensions of political cynicism has empirically been confirmed (Adriaansen & Tiemeijer, 2011). 3 However, previous studies (Aarts & Semetko, 2003;De Vreese & Elenbaas, 2008;Leshner & McKean, 1997) did not yield a significant relationship between political interest and political cynicism. 11 Theoretically speaking, it would be most appropriate to also include variables as political knowledge and interest or exposure to other news sources as endogenous variables.…”
Section: Soft News With Hard Consequences?mentioning
confidence: 68%
“…Corner and Pels 2003;Habermas 2006;Entman 2007). Deriving from Huizinga's (1955) study on the role of play in culture, the game or play metaphor is commonly used in various fields of journalism research (Corner and Pels 2003;De Vreese and Elenbaas 2008;Aalberg, Strömbäck, and De Vreese 2011). According to Huizinga, elements of play are part of and shape numerous aspects of society and culture, for example in law or the arts, but also in politics.…”
Section: Birte Schohaus Et Almentioning
confidence: 99%
“…In studies of political news coverage, especially of campaign strategies and election coverage, the strategic game frame, including horse race, game, and strategy frames, is one of the key concepts (Patterson 1993;De Vreese and Elenbaas 2008;Aalberg, Strömbäck, and De Vreese 2011). Predominantly, but not exclusively, in election campaigns media tend to cover political news as a competition with winners and losers (horse race and game frame) and attempt to reveal the strategies for winning the elections (strategy frame).…”
Section: Agon: Competition Between Talk Shows Producers and Pr Advisorsmentioning
confidence: 99%